A cumulate syenite in the upper part of the Hongge-layered mafic–ultramafic intrusion, Emeishan large igneous province, SW China - Shellnutt, J. Gregory (International journal of earth sciences : Geologische Rundschau, 2021)
Many silicic plutonic rocks of the Late Permian Emeishan large igneous province (ELIP) are spatially and temporally related to oxide ore-bearing layered mafic–ultramafic intrusions. Their association suggests that there may be a petrogenetic link between the two rock types where the layered intrusion represents the cumulate portion of the magma system and the silicic rocks are the residual liquid portion. An alkali feldspar syenite collected in close spatial association with the Hongge-layered mafic–ultramafic intrusion yielded a weighted-mean zircon U–Pb age of 261.5 ± 2.4 Ma with a corresponding weighted-mean ε Hf ( t ) value of + 6.5 ± 0.5. The Hongge syenite is alkalic, metaluminous, and ferroan and somewhat similar to other A-type granitoids of the ELIP but, it is composed of ~ 90 vol% alkali feldspar. The rocks have initial 87 Sr/ 86 Sr ratios of 0.70570 and 0.70515 and ε Nd ( t ) values of − 0.3 and + 1.4. Rhyolite-MELTS and isotopic modeling indicate that the Hongge syenite is likely produced by crystal accumulation of a residual silicic liquid derived from a mafic parental magma that experienced localized crustal contamination during emplacement. Moreover, the age, location, and composition of the Hongge syenite suggests that it is the uppermost portion of the Hongge-layered intrusion and is representative of the residual silicic liquid of the mafic magmas that form the plagioclase-rich cumulate gabbros of the upper zone.